Chemical process technology. - Moulijn, Jacob Adriaan, 1942-; Makkee, Michiel, 1954-; Van Diepen, Annelies E., ....- (Chichester : Wiley, 2001)
Chemical Process Technology is a comprehensive introduction, examining both the fundamental concepts and applied nature of this subject. Modern process development relies on a knowledge of many different disciplines and an application and integration of this knowledge. Chemical Process Technology provides an essential bridge between the chemical sciences and the chemical industry. It enables the reader to integrate fundamental knowledge of the basic disciplines, to understand the most important chemical processes, and to apply this knowledge and understanding to industrial processes. This innovative textbook examines both large-scale and small-scale chemical and biotechnology industries and aims to bring to life the concepts that form the basis of the process industry. Starting with a general look at the industry, subsequent chapters examine different processes in greater detail. Emphasis tends to be placed on chemical reactions and the reactor, both at the heart of each process, but coverage also includes feed pre-treatment and product separation.